Reducing cassava FLW and associated GHG emissions through mobile processing units - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Cassava, is a hotspot crop in terms of FLW volume in Sub Sahara Africa. This is related to high perishability of the crop and poor infrastructure connections between farming areas and processing locations. This study analyses the effects of mobile processing unit (travelling between production regions) the converts the perishable root in a more stable product. Result: large reduction of FLW and, despite being less energetically efficient than a large scale central factory, net reduction of GHG per kg end-product.